Assessing service quality and customer experience in relation to customer satisfaction in organizing mice events - Parasuari, Ni Komang Lia; Putra, I Komang Mahayana; Wajdi, Majid; Zailani, Suhaiza (Journal of Commerce, Management, and Tourism Studies, 2026)
The growth of the MICE (Meeting, Incentive, Conference, and Exhibition) sector has become an important driver of tourism and economic development in Bali, making the delivery of high-quality services and memorable customer experiences increasingly essential for hospitality businesses. Despite the increasing demand for MICE services, maintaining a high level of customer satisfaction remains a challenge for some hospitality providers, including Four Points by Sheraton Bali Ungasan. This study investigates the relationship between service quality, customer experience, and customer satisfaction among MICE clients at the hotel. A quantitative approach was employed using questionnaire-based surveys administered to 87 Persons in Charge (PICs) representing organizations that conducted MICE events at the hotel during 2024–2025. Respondents were selected through random sampling. Data analysis was carried out using SPSS 30, including classical assumption testing, multiple regression analysis, hypothesis testing, and coefficient of determination analysis. The findings reveal that service quality contributes significantly to customer satisfaction, as indicated by a t-value of 13.574, exceeding the critical value of 1.663. Likewise, customer experience demonstrates a significant positive contribution to customer satisfaction, with a t-value of 12.707, which is also greater than the critical value. Furthermore, the combined effect of service quality and customer experience on customer satisfaction is statistically significant, as reflected by an F-value of 147.907, surpassing the F-table value of 3.11, and a significance level below 0.05. These results emphasize that both service quality and customer experience are key determinants of customer satisfaction in the context of MICE event management and highlight their strategic importance for enhancing the competitiveness of hospitality establishments in Bali.